Modulation of T Cell Responses by Fucoidan to Inhibit Osteogenesis - Huang, Hailin; Guo, Fangze; Deng, Xuyang; Yan, Mingzhe; Wang, Danyang; Sun, Zhanyi; Yuan, Changqing; Zhou, Qihui (Frontiers in Immunology, 2022)
Fucoidan has sparked considerable interest in biomedical applications because of its inherent (bio)physicochemical characteristics, particularly immunomodulatory effects on macrophages, neutrophils, and natural killer cells. However, the effect of fucoidan on T cells and the following regulatory interaction on cellular function has not been reported. In this work, the effect of sterile fucoidan on the T-cell response and the subsequent modulation of osteogenesis is investigated. The physicochemical features of fucoidan treated by high-temperature autoclave sterilization are characterized by UV–visible spectroscopy, X-ray diffraction, Fourier transform infrared and nuclear magnetic resonance analysis. It is demonstrated that high-temperature autoclave treatment resulted in fucoidan depolymerization, with no change in its key bioactive groups. Further, sterile fucoidan promotes T cells proliferation and the proportion of differentiated T cells decreases with increasing concentration of fucoidan. In addition, the supernatant of T cells co-cultured with fucoidan greatly suppresses the osteogenic differentiation of MC3T3-E1 by downregulating the formation of alkaline phosphatase and calcium nodule compared with fucoidan. Therefore, our work offers new insight into the fucoidan-mediated T cell and osteoblast interplay.